2003
DOI: 10.1093/jn/133.3.752
|View full text |Cite
|
Sign up to set email alerts
|

A Soybean Peptide Isolate Diet Promotes Postprandial Carbohydrate Oxidation and Energy Expenditure in Type II Diabetic Mice

Abstract: The aim of the present study was to determine the effects of dietary proteins on the oxidation of dietary carbohydrate and lipids in type II diabetic mice. KK-A(y) strain mice were provided free access to a high fat diet (30% of energy as fat) for an initial 4-wk period to induce diabetes. To reduce body weight gain, the mice were subsequently fed restrictive isoenergetic and isonitrogenous diets (35% of energy as protein and 5% as fat) based on either casein or soy protein isolate hydrolysate (SPI-H) for 4 wk… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
33
1

Year Published

2004
2004
2020
2020

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 54 publications
(35 citation statements)
references
References 26 publications
1
33
1
Order By: Relevance
“…5,9) The result that the fecal TG content in the rats in the SPI group was almost the same as that in the rats in the CAS group (Table 2) suggests that TG absorption from rat digestive organs was unaffected by dietary proteins. Previous studies have demonstrated that dietary soy peptides increase the excretion of fecal TG in genetically obese type II diabetic mice, 21,22) which does not coincide with the results of the present study. The increased fecal total lipid concentration of SPI-fed rats in the present study might be due to increased fecal steroid excretion, as shown in previous reports, 23,24) which might contribute to a decrease in hepatic TC levels.…”
Section: Discussioncontrasting
confidence: 97%
“…5,9) The result that the fecal TG content in the rats in the SPI group was almost the same as that in the rats in the CAS group (Table 2) suggests that TG absorption from rat digestive organs was unaffected by dietary proteins. Previous studies have demonstrated that dietary soy peptides increase the excretion of fecal TG in genetically obese type II diabetic mice, 21,22) which does not coincide with the results of the present study. The increased fecal total lipid concentration of SPI-fed rats in the present study might be due to increased fecal steroid excretion, as shown in previous reports, 23,24) which might contribute to a decrease in hepatic TC levels.…”
Section: Discussioncontrasting
confidence: 97%
“…The reduction in body fat content seen in the 10-day study concurs with reduced body fat after legume protein consumption reported by other investigators in both laboratory animal [28,29] and human [30] studies -the proposed mechanisms have included activity of vegetable protein peptides on carbohydrate oxidation and energy expenditure [31] or a direct activity of these peptides on body fat metabolism such as through reduced lipogenic enzyme expression [28] . The contradictory effects on body fat seen in the two present rat studies are difficult to compare due to the differences in feeding time and restriction.…”
Section: Discussionsupporting
confidence: 86%
“…28,29) Some experiments have focused on the regulation of the gene expression of uncoupling proteins (UCPs) by dietary proteins, which could be important for studying energy expenditure. 30) Dietary supplementation of epigallocatechin gallate-a green tea bioactive polyphenol-reduces body fat accumulation and upregulates liver UCP2 mRNA in mice with diet-induced obesity.…”
Section: Effect Of Kted On Vomentioning
confidence: 99%